THE ROLE OF INDEPENDENT EDUCATION IN THE FORMATION OF INNOVATIVE ACTIVITY OF A SPECIALIST - Arziev A. S.; Embergenova N. K. (Journals Park Publishing, 2024)
In this article, future professionals study independently in relation to their abilities, talents, opportunities, interests, future professionals learn to develop students' cognitive abilities, study aspects that need to be taken into account taking into account students' independent learning activities, the innovative activity of future specialists is widely highlighted the ways of development, the role and importance of forming students' creative abilities in the process self-study.
Keywords: formation of independent innovative creative ideas, innovative activity, independent learning, creativity, organizational skills, independent activity.